Perancangan Sistem Informasi Pembayaran Sekolah Menggunakan Model Rapid Application Development (RAD) - Joko Pramono; Besus Maula Sulthon Besus Maula Sulthon (KLIK: Kajian Ilmiah Informatika dan Komputer, 2022)
In today's era of globalization, information technology is advancing rapidly. Information obtained because of technological devices such as computers that were created to facilitate human work, especially in the IT field. SMA Muhammadiyah 18 Jakarta is in dire need of an information system to support school needs. For this reason, the author tries to make research on the payment system at SMA Muhammadiyah 18 Jakarta which is currently not computerized. SMA Muhammadiyah 18 Jakarta is a business charity engaged in education under the auspices of the Muhammadiyah Cipulir College, Kebayoran Lama Branch. The existing school payment system is still done manually. Starting from the process of receiving payments to making reports, making it possible during the process there were errors in recording, less accurate reports made and delays in finding the required data. The design of a payment information system is the best solution to solve the problems that exist in this school. Therefore, a computerized system is better than a manual system so that it runs more effectively, efficiently and the current payment system is more conducive than the previous system. The result of this research is a payment system design that utilizes information technology that can solve various problems that occur in the current system.